2019
DOI: 10.3390/toxins11020077
|View full text |Cite
|
Sign up to set email alerts
|

Biological System Responses of Dairy Cows to Aflatoxin B1 Exposure Revealed with Metabolomic Changes in Multiple Biofluids

Abstract: Research on mycotoxins now requires a systematic study of post-exposure organisms. In this study, the effects of aflatoxin B1 (AFB1) on biofluids biomarkers were examined with metabolomics and biochemical tests. The results showed that milk concentration of aflatoxin M1 changed with the addition or removal of AFB1. AFB1 significantly affected serum concentrations of superoxide dismutase (SOD) and malon dialdehyde (MDA), SOD/MDA, and the total antioxidant capacity. Significant differences of volatile fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 80 publications
6
39
1
3
Order By: Relevance
“…These results agree with our earlier study that showed a similar trend using 1H-NMR [12]. This study also agrees with a recent study that reported reduced concentrations of some amino acids such as leucine, isoleucine, valine, and phenylalanine in dairy cows exposed to 40 µg/kg aflatoxin B 1 (AFB1) for 7 days [8].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results agree with our earlier study that showed a similar trend using 1H-NMR [12]. This study also agrees with a recent study that reported reduced concentrations of some amino acids such as leucine, isoleucine, valine, and phenylalanine in dairy cows exposed to 40 µg/kg aflatoxin B 1 (AFB1) for 7 days [8].…”
Section: Resultssupporting
confidence: 93%
“…Consequently, most studies have focused on the use of sequestering agents such as clay and Saccharomyces cerevisiae-based additives to counteract the negative effects of aflatoxin on performance and reduce its transfer to animal products [6]. Most of these studies have evaluated the effects of aflatoxins with or without sequestering agents on the metabolic status of ruminants using few biochemical parameters such as plasma liver enzymes and blood cell counts [6,7], which offer very little in terms of metabolic inferences [8]. A comprehensive analysis of the metabolic profile of animals to aflatoxin exposure is needed to reveal a robust metabolic inference and identify biomarkers of aflatoxin ingestion, which may allow early detection of aflatoxicosis, poisoning caused by ingesting aflatoxins, in livestock.…”
Section: Introductionmentioning
confidence: 99%
“…Ruminants, as a consequence of their characteristic four-chamber stomachs, are considered to be less susceptible to mycotoxins than monogastric species, because mycotoxins can be partially eliminated by the rumen microbiota. However, the ruminal microbial detoxification varies depending on dietary changes or as a result of metabolic diseases [64,67,68]. The maximum limit of AFB 1 has been set by the European Union at 2 µg/kg in all cereals and all cereal-derived products.…”
Section: Aflatoxinsmentioning
confidence: 99%
“…While ruminants are considered less susceptible to mycotoxins than monogastrics, ruminant mycotoxicoses do occur and are problematic for animal health and welfare, for a detailed review on ruminant mycotoxicosis, see [ 58 ]. Aflatoxin B1 (AB1) is a well-studied mycotoxin; its effects and/or potential biomarkers for exposure in dairy cattle plasma [ 59 , 60 ], as well as rumen fluid and milk [ 61 ], have been investigated with metabolomics-based methods. The non-ruminant (porcine) colonic microbiota, namely its functional biodiversity, is impacted by Fusarium mycotoxins [ 62 ]; however, despite this, and the utility of NGS and metabolomics in evaluating animal productivity, integrating these separate data sets towards understanding systemic biological responses and the livestock integrome is yet-to-be widely done.…”
Section: Maintaining Animal Productivity and Wellness In Adverse Ementioning
confidence: 99%